INTERVIEW: Quick, Social and Collaborative - wiki-based user documentation at APC by Schneider Electric - Møller, Margrethe H.; Nielsen, Pernille Bagger; Kalianov, Stanislav (Communication & Language at Work, 2013)
In the software documentation department at APC by Schneider Electric in Kolding, Denmark, Technical Writer Pernille Bagger Nielsen writes user documentation for the software developed by the company. In cooperation with Localization Manager Stanislav Kalianov she reorganised the user documentation for publication as wiki-based documentation on the internet. The new platform supports their strategy of using agile and iterative, topic-based, collaborative writing when developing user documentation. Their experience will interest readers who consider introducing a similar new strategy.